Sistem Pendukung Keputusan Penerima Beasiswa Murid Berprestasi dengan Metode SAW - Nuorma Wahyuni; Erlin Setyaningsih; Adi Hermawansyah; Dila Seltika Canta; Dilla Putri Kinanti; Surmiati Surmiati; Sudarman Sudarman (Journal of Computer System and Informatics (JoSYC), 2023)
This research is a Decision Making System research which purposes to find out the scholarship recipient candidate of the feat student through of the SAW (Simple Additive Weighting) method of the MTsN 1 Penajam Paser Utara. The purpose of this research is to provide of the convenience in the alternative solution in the determining scholarship of the feat student, and to apply of the SAW method in assessing of the scholarship recipient candidate . The Data collection techniques in this research were observation, interview, and literature study. The method is used The SAW. Then it requires the decision maker to determine the level for each the attribute, then the total of score for the alternative is obtained by adding up all the multiplication results between the rating (which can be compared across attributes) and the level of each attribute. The rating for each attribute must be dimension-free in the sense that it has gone through the previous of the normalization process. The basic concept is to find the total leveling of the performance rating for each alternative across all the criterias. The SAW method requires normalization of the decision matrix (X) to scale that can be compared with the existing rating. The sample population taken is from 60 students of MTsN 1 Penajam Paser Utara. From the result of determining the priority of proposed the feat scholarship recipient candidate is using the Simple Additive Weighting method, the student who deserves the best achievement scholarship is M. Indra Saputra who has the highest ranking with a score of 0.916 as the best alternative. The system built can help of the selector team to work in selecting outstanding scholarships and can speed up the selection process and reduce error in determining scholarship recipient.